Hubungan Perilaku Ibu tentang Pemanfaatan Posyandu dengan Status Gizi pada Balita: The Relation of Behavior Mother about the Utilization of Integrated Healthcare Center with Nutritional Status of in Toddlers - Norviana, Eda; Tambunan, Lensi Natalia; Baringbing, Eva Prilelli (Jurnal Surya Medika (JSM), 2022)
Background: Toddlers are children under five years of age marked by a very rapid growth and development process. Infancy is a period that is vulnerable to disease, especially nutritional problems. One of the factors not utilizing integrated healthcare centers regularly will affect the nutritional status of toddlers so that toddlers will experience malnutrition. This is because mothers cannot monitor the growth and development of toddlers if the occurrence of nutritional problems in toddlers cannot be detected early. Objective: The study determined the relationship between maternal behavior regarding the use of integrated healthcare centers with nutritional status in toddlers. Methods: literature review design, Google Scholar data source (2017-2020), articles using Indonesian language, with a population of mothers of toddlers and toddlers. From the search results, the study obtained six inclusion criteria. The research design used was a cross-sectional, descriptive correlation. Results: A total of six articles analyzed stated a relationship between mother’s behavior regarding the use of integrated healthcare centers with nutritional status in toddlers. (p-value 0.000 < 0.05). Conclusion: Based on the study results, six articles stated a relationship between maternal behavior regarding the use of integrated service posts with nutritional status in toddlers. Factors that affect the nutritional status of children under five are the mother’s behavior in the use of integrated service posts; this is because in the use of integrated healthcare centers, there is weighing of children under five, counseling on nutrition, Supplementary Food Provision (PTM) and early detection through Cards Towards Health (KMS) which supports the improvement of nutrition in toddlers and optimal growth.